PENGEMBANGAN DAN IMPLEMENTASI SISTEM PENYEWAAN TANGKI TIMBUN MINYAK KELAPA SAWIT - Martono Martono (Jurnal Processor, 2021)
PT XYZ is a company that provides storage tanks to accommodate palm oil before it is finally shipped via the port. In its business process, PT XYZhas used technology to support its business activities, namely the crude palm oil (CPO) and palm kernel oil (PKO) storage tank rental system that theauthor has built in the previous research. However, concomitant with the development of the company, the need for the system has also increased sothat the existing system does not capable the needs of system users in managing data on tank mutation, free fatty acids tank and shrinkage claims. Basedon these problems, the authors decided to develop a storage tank rental system as a solution to answer the needs of system users. The system developedand implemented in this study is described using the waterfall method, use case diagrams and class diagrams. The palm oil storage tank rentalinformation system that developed in this study has a new additional function as a solution to the problems faced by PT XYZ in managing data. Thefollowing are the functions contained in a system that has been developed and implemented to change user passwords, processing data such as userdata, tanks, vehicles, customers, recipients, receiving and releasing palm oil, tank mutation, free fatty acids tank, claims of shrinkage and revenuereports, palm oil expenditure reports, tank mutation reports, free fatty acids tank reports and shrinkage claims reports.Keywords: Development, Information System, Carter, Storage Tank, Palm Oil.